2013
DOI: 10.1080/13632434.2013.813450
|View full text |Cite
|
Sign up to set email alerts
|

Investigating trait emotional intelligence among school leaders: demonstrating a useful self-assessment approach

Abstract: An exploratory study of two grammar schools in the South East of England is used to justify and demonstrate a self-assessed approach that investigates trait emotional intelligence (EI) among school leaders. First, the theoretical underpinnings of ability and trait EI approaches are critically compared based on recent relevant literature. Then the results from TEIQue-SF, a self-evaluation questionnaire, are presented and discussed. Finally, notwithstanding limitations of the study and the approach taken, we sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…In this case, differences were found between head teachers and the rest of the participants: middle leaders, tutors and, again, teachers. These results revealed higher scores for head teachers in comparison with the other positions, findings that are consistent with a previous study using a self-report instrument (Benson et al, 2014). Further, the greatest differences were found between head teachers and the workers with no leadership role and fewer responsibilities, that is, for teachers.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this case, differences were found between head teachers and the rest of the participants: middle leaders, tutors and, again, teachers. These results revealed higher scores for head teachers in comparison with the other positions, findings that are consistent with a previous study using a self-report instrument (Benson et al, 2014). Further, the greatest differences were found between head teachers and the workers with no leadership role and fewer responsibilities, that is, for teachers.…”
Section: Discussionsupporting
confidence: 92%
“…Previous differences found between head teachers and teachers in the understanding branch could be due to the years of teaching experience, according to the results of Benson et al (2014). Nonetheless, this variable showed no significant results when introduced as a covariate between the understanding branch and the work position variable.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Emotional intelligence is, therefore, a key attribute of innovative and effective school leadership and a complementary resource for creating competent school leaders and developing resilient school communities (Benson et al, 2014). Wong et al (2010) demonstrated that emotional intelligence was positively related to Hong Kong school leaders' performance, job success and satisfaction.…”
Section: Emotional Intelligence Educational Leadership and School Changesmentioning
confidence: 99%